The role of digital marketing and electronic word of mouth in restoring interest and visiting decisions to mangrove ecotourism Kampung Blekok, Situbondo in the new normal era - Abidin, Zainal; Fattah, Mochammad; Wardani, Mentari Puspa; Isniawati, Hani (AGROMIX, 2024)
Introduction: The presence of ecotourism is more oriented toward environmental conservation, utilization of natural resources, cultural preservation, and economic benefits. However, post-COVID-19 pandemic tourist visits to the Kampung Blekok mangrove ecotourism have not recovered, and the condition of the ecotourism is not maintained and is damaged. This research aims to analyze the influence of digital marketing, electronic word of mouth, and interest in visiting on the decision to visit the Kampung Blekok mangrove ecotourism. Methods: Data collection on ecotourism behavior was obtained from 172 respondents using a questionnaire. The data analysis technique used was Structural Equation Modeling Partial Least Squares (SEM-PLS) with WarpPLS version 8.0. Results: The results of the research analysis show that digital marketing and eWOM produce a positive and significant influence on visit intention and decision. The mediating role of visiting interest in the relationship between digital marketing and eWOM on visiting decisions is partial. Mangrove ecotourism managers in Kampung Blekok can optimize digital marketing and eWOM strategies, and adapt to current tourism situations and trends. Conclusion: Digital marketing and eWOM are important in shaping visit interest and determining tourist decisions. Changes in tourist behavior using digital media can be a tool for progressing the ecotourism business by increasing tourists' visiting decisions.